Global Muslim Response to Bandung Halal Tourism Branding - Aping Firman Juliansyah; Agustina Eka Putri; M. Liga Suryadana; Cipta Endyana; Akhmad Kusuma Wardhana (International Journal of Applied Sciences in Tourism and Events, 2021)
The city of Bandung has great potential for halal tourism. In addition to the carrying capacity of natural and human resources, Bandung has been designated by the Indonesian. However, policy makers still have not carried out special branding for halal tourism for the city of Bandung. This study has a purpose to observe the importance of branding for halal tourism in Bandung. This study uses a qualitative approach. The data were collected through questionnaires and literature study. The result showed that the majority of Muslims from various countries consider halal tourism branding important and influence their choice of the city they will visit.